Competing Ion Exchange of Zn and Fe in NaY Zeolite - Indianara C. Ostroski; João H. Dantas; Edson A. Silva; Pedro A. Arroyo; Maria A. S. D. Barros (Adsorption Science & Technology)
This study was aimed at investigating the equilibrium and interactive effects of binary solutions containing Zn +2 and Fe +3 ions in fixed-bed columns of NaY zeolite. To calculate the dynamic equilibrium through isotherms, experiments were carried out in a fixed-bed column. Reagent-grade ZnCl 2 and FeCl 3 ·6H 2 O solutions were mixed with deionized water to prepare the feed solutions with total ion concentrations in the range of 0.5–5.0 meq/ℓ. Experiments were then carried out using Fe 3+ and Zn 2+ ions in the following concentration ratios: 0.75:0.25, 0.50:0.50 and 0.25:0.75. The experimental equilibrium data were then described using Langmuir-type models (binary Langmuir model, Langmuir-type model, Jain and Snoeyink model, and noncompetitive Langmuir model) as well as ion exchange model. Results of our analysis revealed that NaY zeolite has a higher affinity for Zn 2+ than Fe 3+ ions. The equilibrium data were best fit to the Langmuir-type model. Zn 2+ ions are removed through an ion-exchange process while the Fe 3+ ions may be preferentially adsorbed onto the already exchanged zeolitic sites. This equilibrium model was then applied to a dynamic mathematical model. We describe the equilibrium in this model by assuming the binary Langmuir-type model and mass transfer in the zeolite based on the linear driving force model.